Genomics for Weed Science - Horvath, David (Current Genomics, 2010)
Numerous genomic-based studies have provided insight to the physiological and evolutionary processes involved in developmental and environmental processes of model plants such as arabidopsis and rice. However, far fewer efforts have been attempted to use genomic resources to study physiological and evolutionary processes of weedy plants. Genomics-based tools such as extensive EST databases and microarrays have been developed for a limited number of weedy species, although application of information and resources developed for model plants and crops are possible and have been exploited. These tools have just begun to provide insights into the response of these weeds to herbivore and pathogen attack, survival of extreme environmental conditions, and interaction with crops. The potential of these tools to illuminate mechanisms controlling the traits that allow weeds to invade novel habitats, survive extreme environments, and that make weeds difficult to eradicate have potential for both improving crops and developing novel methods to control weeds.